Detection and Monitoring of E-Waste (International Journal of Scientific Research in Science and Technology, 2024)
In this present paper, the national and international e-waste scenario is discussed. With increasing usage waste production is also increasing. Now, the situation is alarming as a huge quantity of waste is generated by India as well as other countries. The condition in India is much worse because about 80 percent of the e-waste generated in the US is exported to India, China, and Pakistan under the name of charity. Waste from electrical and electronic equipment comes under a special category of waste which is the result of industrialization and ever ever-increasing demand for electronic products in daily life. Only 3% of total WEEE-waste generated is recycled properly in India.
Keywords: WEEE; Informal Recycling; Hazards